Globalisation and higher education in Pakistan - AMMAR HUSNAIN KHAN (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper aims to evaluate recent policy reforms that prioritize university autonomy and privatization through higher tuition rates while also addressing the quantity and quality of higher education. High tuition costs undermine the good public status of higher education and are a major social and political concern.Methodology: The researchers in this study used a qualitative approach and based their findings on an extensive review of the relevant literature.Findings: Issues like national education policies, institutional strategies, and cultural concerns must be carefully considered if the internationalization of higher education is to be successful.Novelty/Implications: This research sought to examine the policies aimed at highlighting a definite stance on public financing in the reformation of Pakistan’s higher education system. Policymakers in Pakistan are given actionable advice and policy implications to enhance the quality of higher education for Pakistani students.